Analisis Regresi Ordinal Model Logit untuk Mengidentifikasi Faktor yang Mempengaruhi Indeks Pembangunan Manusia - Yonita Dyah Puji Dwiningtias; Mahmudah Mahmudah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
The Human Development Index (HDI) is an index used to determine the level of quality of human life. HDI became a trend because all local governments are competing to increase the value of their regional HDI. This study aims to identify the factors that influence the HDI of districts/cities in East Java Province in 2017 using the logit model ordinal regression approach. This type of research is a non reactive study using secondary data from the Central Statistics Agency and the East Java Province Health Office in 2017. The study population is all districts/cities of East Java Province. The total research analysis unit was 38 districts/cities. The dependent variable of the study is low, medium, high and very high HDI. The independent variable of the study is the percentage of households behaving clean and healthy, student-teacher ratio (high school level) and open unemployment rate. The results of the analysis using the logit model ordinal regression test (α = 5%) prove there is an influence between the open unemployment rate variable (p = 0.006; β = 0.790) on the HDI. The variable percentage of households behaving clean and healthy and student-teacher ratio (high school level) has no effect on HDI. Both central and regional governments are expected to be able to improve human development in all sectors, especially health, education and the economy.